2022
DOI: 10.1016/j.puhe.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

College reopening and community spread of COVID-19 in the United States

Abstract: Objective. After months of lockdown due to the COVID-19 outbreak, the U.S. postsecondary institutions implemented different instruction approaches to bring their students back for the Fall 2020 semester. Given public health concerns with reopening campuses, the study evaluated the impact of Fall 2020 college reopenings on COVID-19 transmission within the 632 U.S. university counties. Study design. This was a retrospective and observational study. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, it has now become clear that the reopening of schools does impact community infection rates, even though appropriate mitigation strategies reduce this effect ( 30 ). There is no doubt that university testing can be effective at limiting the spread of the virus in this setting ( 31 , 32 ), especially when contact tracing has fast turnaround times, as in our study. In addition, the testing center became an educational site for students to gain clinical hours as part of their internships.…”
Section: Discussionsupporting
confidence: 56%
“…However, it has now become clear that the reopening of schools does impact community infection rates, even though appropriate mitigation strategies reduce this effect ( 30 ). There is no doubt that university testing can be effective at limiting the spread of the virus in this setting ( 31 , 32 ), especially when contact tracing has fast turnaround times, as in our study. In addition, the testing center became an educational site for students to gain clinical hours as part of their internships.…”
Section: Discussionsupporting
confidence: 56%
“…College campuses are at risk to develop an high incidence of COVID-19 and become superspreaders for neighboring communities [27]. Meanwhile, more than 80% of our university county sample did not experience a significant case increase in Fall 2020 and there were no significant relationships between opening approaches and community transmission in both maskrequired and non-mask-required states [16]. Referring to the same semester, fall of 2020, County-level COVID-19 incidence decreased in much of the United States in late summer 2020.…”
Section: Introductionmentioning
confidence: 73%
“…If percentage positivity had been stable or declining across the observation period, then efforts on the part of many colleges and universities to conduct or require testing before students' return to campus and their ongoing surveillance efforts might explain an increase in case counts, as a result of increased case discovery. However, the concurrent increases in percentage positivity and in incidence in these counties suggest that higher levels of transmission, in addition to increased case discovery, occurred in these communities [16]. Yet, the New York Times reported that, "When many campuses reopened in the fall, outbreaks raced through dorms, infected hundreds of thousands of students and employees, and spread to the wider community.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not the reopening of a given college or university contributed to higher off-campus COVID transmission will depend on several variables (e.g. whether a school was in a state that mandated mask-wearing) ( 76 ), but in our case the COVID wave that occurred in our university in January 2021 (Wave 1) peaked during the tail end of one which had been ongoing in surrounding counties (compare FIG 2 to supplemental FIG S2 ). This was also true in Aug 2022, when our campus reopened after summer break and experienced Wave 4, which followed the Delta wave that had already begun in surrounding counties.…”
Section: Discussionmentioning
confidence: 98%